Chain arrangements of selectively deuterated poly(ε-caprolactone) copolymers as revealed by neutron scattering. (10th April 2020) - Li, Lengwan; Li, Tianyu; Arras, Matthias M.L.; Bonnesen, Peter V.; Peng, Xiangfang; Li, Wei; Hong, Kunlun
Abstract: The chain arrangement within the crystalline lamellae has been the focus of polymer crystallization. In this study, a series of protiated (H) and deuterated (D) poly(ε-caprolactone) (PCL) blends, block and random copolymers were investigated by small-angle neutron scattering (SANS) measurements. The spatial inhomogeneities of block copolymers were analyzed via Debye-Bueche method and temperature dependence of Flory-Huggins interaction parameter χ in the melt was extracted from fitting the scattering data to the random phase approximation model. Studying the changes of SANS signals further revealed that the copolymers exhibit cooling rate-dependent crystallization behaviors. A unique SANS double-peak pattern was found in D4/D10 50/50 blend and D10-D0-D10 triblock copolymers (where D0, D4, and D10 indicate PCL with different levels of deuteration), as a result of two types of contrasts: scattering length density (SLD) difference between lamellae of different components and density difference between amorphous and lamellar domains. These detailed findings complement our understanding of the complex crystallization processes of deuterated polyesters, which also suggest an avenue for fine control of crystal structures that adds to materials design. Graphical abstract: Image 1 Highlights: Deuterated (D) PCL block and random copolymers were investigated by SANS measurements. The spatial inhomogeneities of D-PCL triblock copolymers were calculated and χ parameters were extracted. Bimodal SANS peaks were found in blends and triblock copolymers, which was resulted from two types of contrasts.